KESINTASAN PASIEN DENGAN METASTASIS LEPTOMENINGEAL YANG DIRAWAT DI BAGIAN NEUROLOGI RUMAH SAKIT KANKER DHARMAIS DAN RSUPN DR CIPTO MANGUNKUSUMO - Elsa Susanti; Rini Andriani; Tiara Aninditha; Henry Riyanto Sofyan (PERDOSNI, 2020)
Introduction: Leptomeningeal metastasis is a condition where malignant cells spread to the leptomening and subarachnoid space. This is an emergency state with incident tends to increase each year. Prognosis is very poor and survival rate is only 10-15 weeks. Aim: To determine survival of leptomeningeal metastasis patients in Cancer Dharmais Hospital and Cipto Mangunkusumo Hospital. Methods: This is a retrospective cohort research based on medical records of leptomeningeal metastasis patients in Cancer Dharmais Hospital and Cipto Mangunkusumo Hospital from January 2018 to June 2019. Clinical examination, liquor cerebral examination, MRI, and histopathological of primary tumours were written. Subjects or family of the subjects were contacted to obtain information about subject’s wellbeing whether they’re still alive or dead. If they’re unreachable they will be excluded. Survival of each subject was determined based on how long the subject remain alive since being diagnosed with leptomeningeal metastasis until the end of observation, which is the end of the research. Results: Sixty two patients were included in the research, 21 were males and 41 were females. Headache was the most frequent symptoms found in the patients (46.8%) followed by cranial nerves deficits (45.2%). Median survival in this research was 13 weeks, no significant differences in survival from haematologic malignancy and solid tumor. Discussion: Median survival of leptomeningeal metastasis patients was 13 weeks, there was no statistically significant difference between survival of heamotologic malignancy and solid tumor. Median survival in leptomeningeal metastasis in this research remain poor regardless the origin of the metastasis. Keywords: Haematologic malignancy, leptomeningeal metastasis, solid tumor, survival